Duodenal perforation and esophageal ischemia following transarterial chemoembolization for hepatocellular carcinoma: A case report. Issue 27 (July 2016) - Kim, Shin Il; Jin, Young-Joo; Cho, Soon Gu; Shin, Woo Young; Kim, Joon Mee; Lee, Jin-Woo
Abstract : Abstract: Transarterial chemoembolization (TACE) is frequently used for treatment of unresectable hepatocellular carcinoma (HCC) and can also be used for case of liver metastases from rectal cancer. Although it is recognized as safe and effective treatment, various complications have been reported. However, post-TACE duodenal perforation with duodenal and esophageal ischemia has not been reported in the literature. A 43-year-old male had experienced duodenal perforation combined with duodenal and lower esophageal ischemia after 8 times of repeated TACE for recurrent and unresectable HCCs, that was confirmed on esophagogastroduodenoscopy and abdominal computed tomography. Interestingly, operative findings showed complete recovery of duodenal ischemia except perforation, and he recovered with just the segmental duodenectomy and gastrojejunostomy. We report a case of duodenal perforation with necrosis and esophageal ischemia after 8th TACE for unresectable HCC. Although this complication is rare and unexpected, it may result in severe sequelae requiring surgical repair. The careful procedure during TACE followed by post-TACE careful monitoring is required in patients with posthepatectomy or repeated TACE, especially in the case with unusual clinical manifestations.